Efficacy of a Modified Hysteroscopic Proximal Tubal Occlusion Technique on IVF Outcomes - Hu, Tao-Tao; Sun, Li; Yuan, Kai; Liu, Wen-Yu; Cai, Yi-ling; Cai, Hua-Lei (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to evaluate whether optimizing the placement of microcoil in the fallopian tube during hysteroscopy could enhance in vitro fertilization-embryo transfer (IVF-ET) pregnancy rates and reduce complications.MethodsA retrospective cohort study included 94 patients with tubal infertility who underwent tubal embolization at Baiyun Hospital of Guizhou Medical University between May 2019 and December 2023. Patients were divided into two groups: Group A (n = 65) used the original technique, while Group B (n = 29) used a modified technique. Effective follow-up data were obtained from 42 patients in Group A (Group Aa) and 15 patients in Group B (Group Ba). Key variables, including the mean time to successful IVF pregnancy, the number of IVF cycles, ongoing pregnancy (gestation ≥12 weeks), and complication rates, were analyzed.ResultsThe mean time to conception was shorter in Group Ba (6.10 months, median = 7.5 months) than in Group Aa (11.58 months, median = 12 months), though not statistically significant (p = 0.092). Similarly, the mean number of IVF cycles required for implantation was slightly lower in Group Ba (1.60) than in Group Aa (1.92), with no significant difference (p = 0.236). However, clinical pregnancy persistence rates were significantly higher in Group Ba (10/14, 71.43%) than in Group Aa (12/32, 37.50%) (χ2 = 4.493, p = 0.034). Additionally, Group Aa reported two cases of post-IVF ectopic pregnancy (2/32), while no such cases were observed in Group Ba.ConclusionOptimizing the proximal tubal plugging site via hysteroscopy may enhance ongoing pregnancy post-IVF-ET. Further studies are needed to explore the relationship between coil positioning depth and ectopic pregnancy risk, as well as to determine the optimal timing for postoperative IVF-ET. Ongoing pregnancy rates differed markedly by occlusion site: unilateral isthmic occlusion (0%) vs. bilateral isthmic occlusion (44.44%, p = 0.059), suggesting a clinical trend. Conversely, interstitial occlusion yielded high and comparable rates (unilateral: 83.33% vs. bilateral: 62.50%, p = 0.393), unaffected by laterality.